A Multidimensional Construction of the Meaning of Income from an Auditor’s Perspective - Harti Novika Wiradhika; Masiyah Kholmi; Eko Handayanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Auditors play a critical role in maintaining the credibility of financial reports and public trust. This study aims to clarify the meaning of income from the perspectives of junior and senior auditors. The research method used is a qualitative descriptive case study approach, through data collection in the form of in-depth interviews, observations, and documentation of auditors working at the public accounting firm. The data was analyzed using NVivo14 software to identify themes in the interview results. The results showed that auditors interpreted their income in four main dimensions, namely the material dimension (fulfillment of needs and future savings), non-material dimension (professional recognition and appreciation for performance), fairness dimension (reflection of equality between workload and compensation and system transparency), and spiritual dimension (income as sustenance predetermined by God, halal, and a blessing). This study contributes by providing a multidimensional understanding of auditors’ income encompassing material, non-material, fairness, and spiritual aspects while offering practical insights for designing more holistic and value-driven compensation systems.